Clinical learning environments: place, artefacts and rhythm. Issue 10 (October 2017) - Sheehan, Dale; Jowsey, Tanisha; Parwaiz, Mariam; Birch, Mark; Seaton, Philippa; Shaw, Susan; Duggan, Alison; Wilkinson, Tim
Abstract : Context: Health care practitioners learn through experience in clinical environments in which supervision is a key component, but how that learning occurs outside the supervision relationship remains largely unknown. This study explores the environmental factors that inform and support workplace learning within a clinical environment. Methods: An observational study drawing on ethnographic methods was undertaken in a general medicine ward. Observers paid attention to interactions among staff members that involved potential teaching and learning moments that occurred and were visible in the course of routine work. General purpose thematic analysis of field notes was undertaken. Results: A total of 376 observations were undertaken and documented. The findings suggest that place (location of interaction), rhythm (regularity of activities occurring in the ward) and artefacts (objects and equipment) were strong influences on the interactions and exchanges that occurred. Each of these themes had inherent tensions that could promote or inhibit engagement and therefore learning opportunities. Although many learning opportunities were available, not all were taken up or recognised by the participants. Conclusions: We describe and make explicit how the natural environment of a medical ward and flow of work through patient care contribute to the learning architecture, and how this creates or inhibits opportunities for learning. Awareness of learning opportunities was often tacit and not explicit for either supervisor or learner. We identify strategies through which tensions inherent within space, artefacts and the rhythms of work can be resolved and learning opportunities maximised.